(untitled) (Modern education and development, 2024)
This study examines the relationship between teacher professional development and student achievement. Utilizing a mixed-methods approach, it investigates how continuous professional learning opportunities impact teacher effectiveness and student outcomes. Data were collected through surveys, interviews, and student performance metrics. The results suggest a significant correlation between ongoing teacher development and improved student performance, highlighting the need for sustained and targeted professional development programs.